Polyamide resin film and package using the film

A polyamide resin film with an aliphatic polyamide resin and styrenic block copolymer addresses bending pinhole resistance and transparency issues across temperature ranges, enhancing packaging performance.

JP2024174924AInactive Publication Date: 2024-12-17MITSUBISHI CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024151590
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polyamide resin films face challenges in maintaining bending pinhole resistance and transparency across a wide temperature range, particularly in low-temperature environments, which is critical for packaging applications.

Method used

A polyamide resin film comprising at least one layer containing an aliphatic polyamide resin and a styrenic block copolymer with specific composition and molecular weight, optimized for biaxial stretching, to enhance bending pinhole resistance and transparency.

Benefits of technology

The film achieves excellent balance of transparency and bending pinhole resistance, ensuring the quality of packaged products from low to room temperature environments, with improved mechanical properties and gas barrier properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174924000003
    Figure 2024174924000003
  • Figure 2024174924000001
    Figure 2024174924000001
  • Figure 2024174924000002
    Figure 2024174924000002
Patent Text Reader

Abstract

To provide a polyamide resin film excellent in bending pinhole resistance and transparency in a wide temperature range from under a low temperature environment to under a normal temperature environment.SOLUTION: The polyamide resin film is provided which has at least one layer of an A layer including an aliphatic polyamide resin (a1) and a styrenic block copolymer (a2), the content of the styrenic block copolymer is 1-20 mass% when the A layer is 100 mass%, the styrenic block copolymer (a2) includes, as copolymer constituents, a styrene monomer unit and an isobutyrene monomer unit, the content of the styrene monomer unit is 5 mass% or more and 30 mass% or less, the weight average molecular weight of the styrene monomer unit is 20,000 or more and 130,000 or less, the haze of the film is 10% or lower, and the number of pin holes by a Gelbo flex test at a temperature of 5°C, a relative humidity of 50%, a flexure of 500 times is 15.0 / 481 cm2 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyamide resin film for use in packaging foodstuffs, medical and pharmaceutical products, industrial parts, etc., and to a package using said film. [Background technology]

[0002] 2. Description of the Related Art Films made of polyamide resins are used in a variety of applications because they are excellent in mechanical properties such as impact resistance and strength, heat resistance, and moldability such as biaxial orientation.

[0003] Furthermore, polyamide resin films have superior impact resistance and mechanical strength compared to other resins; however, in the current market where low-temperature transportation and thinner packaging materials have become more common, further reducing the occurrence of pinholes caused by transportation and friction with other materials during distribution has become an urgent issue. There is therefore a strong demand from the food packaging market and industry for further improvements in the toughness of polyamide resin films, and in particular for improvements in pinhole resistance under a wide temperature range, from low-temperature environments where pinholes are likely to occur to room temperature environments.

[0004] In response to these problems, Patent Document 1 discloses a biaxially oriented polyamide-based laminate film in which a flexibility modifier is blended in the polyamide 6 layer, which is the outermost layer, and a saponified ethylene-vinyl acetate copolymer layer and a polyamide 6 layer that does not contain a flexibility modifier are co-extruded, and examples of the flexibility modifier include polyolefins, polyamide elastomers, and polyester elastomers. Patent Document 2 discloses a polyamide-based multilayer film in which an A layer containing an aliphatic polyamide, a B layer containing 55 to 95 mass % of a saponified ethylene-vinyl acetate copolymer and 5 to 45 mass % of a soft polymer, and a C layer containing an aliphatic polyamide are laminated in this order, and examples of the soft polymer include polyolefin resins, modified polyolefin resins, ionomer resins, polyamide-based elastomers, (meth)acrylic elastomers, and styrene-based elastomers. However, these techniques alone cannot satisfy the market demand for pinhole resistance that has been increasing in recent years, and are also insufficient in terms of transparency. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2010-023242 A [Patent Document 2] JP 2010-131950 A Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above circumstances, an object of the present invention is to provide a polyamide resin film that is excellent in pinhole resistance under bending and transparency over a wide temperature range from low temperature to room temperature. [Means for solving the problem]

[0007] As a result of intensive research into achieving the above object, the present inventors have found that the above-mentioned problems can be solved by providing a film having at least one layer A containing an aliphatic polyamide resin (a1) and a styrene-based block copolymer (a2) having a specific composition and molecular weight, and have completed the present invention described below.

[0008] The first invention is a film having at least one layer A containing an aliphatic polyamide resin (a1) and a styrene-based block copolymer (a2), the content of the styrene-based block copolymer (a2) being 1 to 20% by mass when the layer A is taken as 100% by mass, the styrene-based block copolymer (a2) containing a styrene monomer unit and an isobutylene monomer unit as copolymerization components, the content of the styrene monomer unit being 5% by mass or more and less than 30% by mass, and the weight-average molecular weight being 20,000 or more and 130,000 or less, the haze of the film being 10% or less, and the number of pinholes being 15.0 / 481 cm in a Gelbo flex test at a temperature of 5°C, a relative humidity of 50%, and 500 bending times. 2 The polyamide resin film is characterized in that:

[0009] The film of the first invention is a biaxially stretched film having at least two layers, namely, the layer A and a layer B containing a gas barrier resin, and has a pinhole count of 4.0 / 481 cm under Gelbo flex test conditions of 23° C., 50% relative humidity, and 3,000 flex cycles. 2 It is preferable that it is less than 1000 .mu.m.

[0010] In the first aspect of the present invention, the gas barrier resin of the layer B is preferably a saponified ethylene-vinyl acetate copolymer (b1), the layer B contains the styrene-based block copolymer (a2), and the content of the styrene-based block copolymer (a2) is preferably 1 to 20 mass % when the layer B is taken as 100 mass %.

[0011] In the first aspect of the present invention, the styrene-based block copolymer (a2) is preferably a styrene-isobutylene-styrene block copolymer.

[0012] In the first invention, in cross-sectional observation parallel to the machine direction (MD) or transverse direction (TD) of the film, the maximum horizontal diameter of the dispersed particles of the styrene block copolymer (a2) in the layer A in the MD or TD is preferably 3.0 μm or less.

[0013] In the first invention, it is preferable that the A layer is arranged as the outermost layer.

[0014] The second invention is a package using the polyamide-based resin film of the first invention.

Effect of the Invention

[0015] The polyamide-based resin film of the present invention is excellent in the balance between transparency and flexural pinhole resistance. In particular, since it can have good flexural pinhole resistance in the temperature range from low temperature to normal temperature, by using the film of the present invention as a package, the quality of the packaged product can be maintained well during storage, distribution, display, and until the start of consumer use of the packaged product.

Brief Description of the Drawings

[0016] [Figure 1] Figure 1(a) is a schematic diagram of a cross-section parallel to the TD of the A layer and perpendicular to the film thickness direction (hereinafter, may be referred to as a TD parallel direction cross-section), and Figure 1(b) is a schematic diagram of a cross-section parallel to the MD of the A layer and perpendicular to the film thickness direction (hereinafter, may be referred to as an MD parallel direction cross-section).

Embodiments for Carrying Out the Invention

[0017] Hereinafter, the present invention will be described in detail. When described as "X to Y" (X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", and also includes the meaning of "preferably larger than X" and "preferably smaller than Y". The polyamide-based resin film of the present invention (hereinafter, may be referred to as "the film of the present invention") has at least one A layer containing an aliphatic polyamide-based resin (a1) and a styrene-based block copolymer (a2).

[0018] (Aliphatic polyamide-based resin (a1)) As the aliphatic polyamide resin (a1) used in the present invention, the ring-opening polymer of the following cyclic lactams can be preferably used. Specifically, these include acetolactam (polyamide 2), propiolactam (polyamide 3), butyrolactam (polyamide 4), valerolactam (polyamide 5), caprolactam (polyamide 6), enantholactam (polyamide 7), caprylolactam (polyamide 8), pelargolactam (polyamide 9), caprinolactam (polyamide 10), laurolactam (polyamide 12), etc. Polycondensates of the following aminocarboxylic acids can also be suitably used, such as aminopropionic acid (polyamide 3), aminobutyric acid (polyamide 4), aminovaleric acid (polyamide 5), aminocaproic acid (polyamide 6), aminoenanthic acid (polyamide 7), aminocaprylic acid (polyamide 8), aminopelargonic acid (polyamide 9), aminocapric acid (polyamide 10), and aminolauric acid (polyamide 12).

[0019] Furthermore, polycondensates of the following dicarboxylic acids and diamines can also be suitably used. Specifically, polytetramethylene adipamide (polyamide 46), polytetramethylene sebacamide (polyamide 410), polytetramethylene dodecamide (polyamide 412), polyhexamethylene adipamide (polyamide 66), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecamide (polyamide 612), polynonamethylene adipamide (polyamide 96), polynonamethylene sebacamide (polyamide 910), polynonamethylene dodecamide (polyamide 912), polydecamethylene adipamide (polyamide 106), polydecamethylene sebacamide (polyamide 1010), polydecamethylene dodecamide (polyamide 1012), etc. These may be copolymerized as a single component or as a combination of multiple components, and any copolymerization method such as random copolymerization, block copolymerization, or graft copolymerization may be used. Among these aliphatic polyamide resins, polyamide 6, polyamide 66, and polyamide 6,66 are preferred because they have an excellent balance of heat resistance, moldability, water absorption, and mechanical strength, and polyamide 6 is particularly preferred because of its versatility and high economical value.

[0020] (Styrene-based block copolymer (a2)) The styrene-based block copolymer (a2) used in the present invention contains styrene monomer units and isobutylene monomer units as copolymerization components, has a styrene monomer unit content of 5% by mass or more and less than 30% by mass, and has a weight average molecular weight of 20,000 or more and 130,000 or less.

[0021] The styrene-based block copolymer (a2) may have at least one styrene block and at least one isobutylene block in the molecule, and the structure is not particularly limited. For example, it may have any molecular chain form such as a linear ABA triblock structure, an AB diblock structure, a branched chain having two or more branches, or a star (radial) structure. Among them, from the viewpoint of adhesion between the sea / island phase with the aliphatic polyamide resin (a1) and adhesion with other layers, a linear ABA triblock structure, an AB diblock structure, and a mixture thereof are preferred, and a linear ABA triblock structure is more preferred.

[0022] Examples of monomers constituting the styrene block include styrenes such as styrene, α-methylstyrene, 2-methylstyrene, 4-methylstyrene, 4-propylstyrene, 4-t-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 2,4,6-trimethylstyrene, monofluorostyrene, difluorostyrene, monochlorostyrene, dichlorostyrene, methoxystyrene, and t-butoxystyrene; vinyl group-containing aromatic compounds such as vinylnaphthalenes such as 1-vinylnaphthalene and 2-vinylnaphthalene; and vinylene group-containing aromatic compounds such as indene and acenaphthylene. The monomer units constituting the styrene block may be of one type or two or more types, but among them, those consisting of styrene or units derived from styrene are particularly preferred.

[0023] The styrene block may be one in which the aromatic ring is hydrogenated, and can generally be obtained by producing a block copolymer and then hydrogenating the copolymer. From the viewpoint of improving the gas barrier properties of the present film, the hydrogenation rate of the aromatic ring is preferably 50% by mass or more, more preferably 80% by mass or more. The hydrogenation method and reaction form of the aromatic ring are not particularly limited, but a method that increases the hydrogenation rate and causes less polymer chain scission reaction is preferred.

[0024] An example of a monomer that constitutes an isobutylene block is isobutylene. Specific examples of copolymers of styrene blocks and isobutylene blocks include styrene-isobutylene block copolymers (SIB), styrene-isobutylene-styrene block copolymers (SIBS), and combinations of these, such as SIBS / SIB, which are preferred due to their excellent thermal stability.

[0025] The styrene-based block copolymer (a2) may be a functional group-modified copolymer containing at least one functional group selected from the group consisting of an acid anhydride group, a carboxyl group, a hydroxyl group, an amino group, an isocyanate group, and an epoxy group, or a mixture of a modified copolymer and an unmodified copolymer.

[0026] The copolymerization composition ratio of the styrene-based block copolymer (a2) is 5% by mass or more and less than 30% by mass of styrene monomer units. The lower limit is preferably 10% by mass or more, more preferably 15% by mass or more. The upper limit is preferably 28% by mass or less, more preferably 25% by mass or less. If the styrene monomer unit is less than 30% by mass, the rubber hardness is low and excellent impact resistance can be imparted when blended with the aliphatic polyamide resin (a1), whereas if it is 5% by mass or more, excellent moldability is achieved, such as the styrene block copolymers (a2) being able to be dry blended without blocking with each other. The isobutylene monomer unit content is preferably 70% by mass or more and less than 95% by mass, with the lower limit being more preferably 72% by mass or more and even more preferably 75% by mass or more.The upper limit is preferably 90% by mass or less and even more preferably 85% by mass or less. When a plurality of styrene blocks or isobutylene blocks are present, the composition ratio (mass %) is the sum of the plurality of styrene blocks or isobutylene blocks.

[0027] The weight average molecular weight of the styrene block copolymer (a2) is 20,000 or more and 130,000 or less. The lower limit is preferably 40,000 or more, more preferably 60,000 or more. The upper limit is preferably 110,000 or less, more preferably 100,000 or less. When the weight average molecular weight is 130,000 or less, the flowability of the styrene block copolymer (a2) is good, and when mixed with the fatty acid polyamide resin (a1), the formability and processability of the film are good. In particular, since fine dispersed particles of the styrene block copolymer (a2) can be formed, the bending pinhole resistance can be improved in a wide temperature range from low temperature to room temperature. On the other hand, when the weight average molecular weight is 20,000 or more, the mechanical properties such as impact resistance and formability of the film are good.

[0028] The styrene-based block copolymer (a2) preferably has a type A durometer hardness of 15 or more and 50 or less. The lower limit is more preferably 18 or more, and even more preferably 20 or more. The upper limit is more preferably less than 45, and even more preferably less than 40. The Type A durometer hardness of the styrene-based block copolymer (a2) depends on the copolymerization composition ratio, molecular weight, and block structure, and can impart flexibility to the film when it is 50 or less. Furthermore, when the Type A durometer hardness is 15 or more, there is little blocking between the styrene-based block copolymers (a2), resulting in good productivity. The type A durometer hardness can be measured by the method described in JIS K6253-3, by contacting a pressure plate with a test piece and reading the value after 15 seconds.

[0029] When the total amount of the aliphatic polyamide resin (a1) and the styrene-based block copolymer (a2) in the A layer is taken as 100% by mass, the content of the styrene-based block copolymer (a2) is preferably 1 to 20% by mass, more preferably 2 to 15% by mass, and even more preferably 3 to 12% by mass. If it is 1% by mass or more, a sufficient effect of improving pinhole resistance can be obtained. If it is 20% by mass or less, it is possible to sufficiently maintain the oxygen gas barrier property and mechanical strength of the present film.

[0030] In Layer A of this film, the styrene-based block copolymer (a2) is dispersed in the form of particles in the aliphatic polyamide resin (a1), with (a1) forming a sea-like dispersion and (a2) forming islands (see Figures 1(a) and (b)). In observing a cross section parallel to the machine direction (MD) or transverse direction (TD) of the present film, the maximum horizontal diameter of dispersed particles of the styrene block copolymer (a2) in layer A in the MD or TD is preferably 3.0 μm or less, more preferably 2.0 μm or less. The maximum diameter in the horizontal direction means the maximum diameter of dispersed particles observed when the film is cut perpendicular to the thickness direction and observed by cross-sectional staining TEM at a magnification of 2000. By dispersing a large number of particles of 3.0 μm or less, the transparency and bending pinhole resistance of the film are both good.

[0031] The aspect ratio (major axis / minor axis) of the length in the film horizontal direction (major axis) to the length in the film thickness direction (minor axis) of the dispersed particles of the styrene block copolymer (a2) in the A layer is preferably 2 or more, more preferably 5 or more. There is no particular upper limit. With an aspect ratio of 2 or more, the particles become thin in the horizontal direction and are dispersed in large numbers, so that the styrene block copolymer (a2) is present all over the film in the horizontal direction, making it difficult for pinholes to occur even if stress concentration occurs due to bending of the film. In particular, when the above maximum diameter and aspect ratio are satisfied in a low temperature environment in the form of a biaxially stretched film, the effect of pinhole resistance is remarkable.

[0032] In addition, when the maximum diameter of the dispersed particles of the styrene block copolymer (a2) in the A layer is 3.0 μm or less in the horizontal direction when observed in either the machine direction (MD) or the width direction (TD) of the film, and the diameter is 4.0 μm or more, preferably 5.0 μm or more when observed in the cross section in the other film direction, the linear cut property in the other film direction is good. For example, when the maximum diameter of the dispersed particles in the width direction (TD) is 3.0 μm or less and the maximum diameter of the dispersed particles in the machine direction (MD) is 4.0 m or more, the pinhole resistance and transparency of the film and the linear cut property in the machine direction (MD) of the film are good (see FIG. 1(a)(b)). In particular, by combining pinhole resistance, transparency, and straight-cutting properties in the form of a biaxially oriented film, when the film is used as a packaging material, it not only improves the preservation and visibility of the contents, but also makes it easier for users to open, thereby improving convenience.

[0033] (Other ingredients) Layer A mainly contains the above-mentioned components (a1) and (a2), and may further contain other components such as aromatic polyamide resins within the range that does not impair the properties of the film of the present invention. Here, the term "main component" means that the component is contained in an amount of 50% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on the layer containing it (100% by mass).

[0034] Examples of aromatic polyamide resins and alicyclic polyamide resins which may be contained in layer A include polytetramethylene terephthalamide (polyamide 4T), polypentamethylene terephthalamide (polyamide 5T), poly-2-methylpentamethylene terephthalamide (polyamide M-5T), polyhexamethylene hexahydroterephthalamide (polyamide 6T), polynonamethylene terephthalamide (polyamide 9T), polydecamethylene terephthalamide (polyamide 10T), polyundecamethylene terephthalamide (polyamide 11T), polydodecamethylene terephthalamide (polyamide 12T), polymetaxylylene adipamide (polyamide MXD6), polyparaxylylene adipamide (polyamide PXD6), polymetaxylylene sebacamide (polyamide MXD10), polyparaxylylene sebacamide (polyamide MXD11T), and polyparaxylylene sebacamide (polyamide MXD11T). Semicrystalline polyamide resins such as polyhexamethylene isophthalamide (polyamide 6I), polybis(3-methyl-4-aminohexyl)methane terephthalamide (polyamide PACMT), polybis(3-methyl-4-aminohexyl)methane isophthalamide (polyamide PACMI), polybis(3-methyl-4-aminohexyl)methane tetradecamide (polyamide PACM12), and polybis(3-methyl-4-aminohexyl)methane tetradecamide (polyamide PACM14) can be suitably used. These may be copolymerized as a single component or as a combination of multiple components. Any copolymerization method such as random copolymerization, block copolymerization, and graft copolymerization may be used.

[0035] In addition, the A layer can contain additives such as heat stabilizers, antioxidants, ultraviolet absorbers, weathering agents, lubricants, fillers, nucleating agents, plasticizers, foaming agents, antiblocking agents, antifogging agents, flame retardants, dyes, pigments, stabilizers, coupling agents, and impact resistance improvers within a range that does not impair the physical properties of the film of the present invention.

[0036] By providing a B layer made of a gas barrier resin, the film of the present invention can be imparted with gas barrier properties, which is useful for preventing spoilage of the contents and enhancing long-term storage stability when used as a packaging film. As the gas barrier resin, known resins can be used. For example, polyvinyl alcohol (PVA), saponified ethylene-vinyl acetate copolymer (EVOH), metaxylylenediamide (MXD6 nylon), and polyvinylidene chloride (PVDC) can be mentioned. Among them, saponified ethylene-vinyl acetate copolymer (EVOH) is preferable in terms of oxygen gas barrier properties.

[0037] (Saponified ethylene-vinyl acetate copolymer (b1)) The saponified ethylene-vinyl acetate copolymer (b1) (EVOH) used in the present invention is a copolymer obtained by saponifying a copolymer of ethylene and vinyl acetate with an alkali catalyst or the like. The ethylene content in the saponified ethylene-vinyl acetate copolymer is not particularly limited, but from the viewpoint of film-forming stability of the film, generally 20 mol% or more is preferable, more preferably 24 mol% or more. On the other hand, from the viewpoint of gas barrier properties, the upper limit of the ethylene content is preferably 48 mol% or less, more preferably 38 mol% or less, and still more preferably 30 mol% or less. Also, the saponification degree of the saponified ethylene-vinyl acetate copolymer (b1) is preferably 96% or more, more preferably 98% or more. In the film of the present invention, when the ethylene content and the saponification degree in the saponified ethylene-vinyl acetate copolymer (b1) are within the above ranges, the balance between film-forming properties and gas barrier properties is excellent. Therefore, coextrusion with an aliphatic polyamide-based resin and forming processes such as biaxial stretching become possible.

[0038] Furthermore, the saponified ethylene-vinyl acetate copolymer (b1) may be modified in various ways as necessary, and may be a mixture of a modified saponified ethylene-vinyl acetate copolymer and a saponified ethylene-vinyl acetate copolymer. Examples of the modified ethylene-vinyl acetate copolymer saponification product include ethylene-vinyl acetate copolymer saponification products modified with propylene, isobutene, etc., ethylene-vinyl acetate copolymer saponification products modified with at least one α-olefin having 3 to 30 carbon atoms, modified ethylene-vinyl acetate copolymer saponification products obtained by graft polymerization of acrylic acid ester, modified ethylene-vinyl acetate copolymer saponification products obtained by saponifying a terpolymer consisting of (meth)acrylic acid ester-ethylene-vinyl acetate, modified ethylene-vinyl acetate copolymer saponification products in which the hydroxyl groups of ethylene-vinyl acetate copolymer saponification product are modified with cyanoethyl groups, modified ethylene-vinyl acetate copolymer saponification products containing polyester graft products obtained by depolymerizing polyester with vinyl alcohol, modified ethylene-vinyl acetate copolymer saponification products obtained by saponifying a copolymer of vinyl acetate-ethylene-silicon-containing olefinically unsaturated monomer ... a pyrrolidone ring-containing monomer, modified ethylene-vinyl acetate copolymer saponified product obtained by saponifying a terpolymer consisting of acrylamide-ethylene-vinyl acetate; modified ethylene-vinyl acetate copolymer saponified product obtained by saponifying a terpolymer consisting of allyl acetate-ethylene-vinyl acetate; modified ethylene-vinyl acetate copolymer saponified product obtained by saponifying a terpolymer consisting of isopropenyl acetate-ethylene-vinyl acetate; modified ethylene-vinyl acetate copolymer saponified product in which a polyether component is added to the end of a saponified ethylene-vinyl acetate copolymer; modified ethylene-vinyl acetate copolymer saponified product in which a polyether component is added in the form of a graft as a branch polymer of a saponified ethylene-vinyl acetate copolymer; and modified ethylene-vinyl acetate copolymer saponified product in which an alkylene oxide is added to a saponified ethylene-vinyl acetate copolymer.

[0039] (Other Ingredients) Layer B contains a gas barrier resin as a main component, and may contain other resins or components as long as the properties of the film of the present invention are not impaired. Here, the term "main component" means that the component is contained in an amount of 50% by mass or more, preferably 80% by mass or more, based on the layer containing it (100% by mass).

[0040] Thermoplastic elastomer (b2) For example, in order to improve the flexibility of the B layer and improve the pinhole resistance of the film, a thermoplastic elastomer (b2) can be mixed. For example, known polyolefin elastomers, polyamide elastomers, (meth)acrylic elastomers, polyester elastomers, styrene elastomers, and modified products thereof can be mentioned, and it is preferable to use one or more from these groups. Examples of the modifying component include unsaturated carboxylic acids such as maleic anhydride and / or their anhydrides, glycidyl acid, amines, epoxies, isocyanates, etc., and the modification rate is preferably 0.01 to 10 mass%. In addition, block copolymers using polyalkylene ether glycol as the soft segment of polyamide elastomers or polyester elastomers are preferable.

[0041] Examples of styrene-based elastomers include styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-ethylene / propylene copolymer (SEP), styrene-ethylene / propylene-styrene block copolymer (SEPS), styrene-ethylene / butylene-styrene block copolymer (SEBS), styrene-ethylene-ethylene / propylene-styrene block copolymer (SEEPS), styrene-isobutylene block copolymer (SIB), and styrene-isobutylene-styrene block copolymer (SIBS).

[0042] From the viewpoints of having good compatibility with the saponified ethylene-vinyl acetate copolymer (b1) of Layer B, fine dispersion, little decrease in film transparency, and improved impact resistance and pinhole resistance, polyamide-based block copolymers and polyester-based block copolymers using polyalkylene ether glycol as a soft segment, as well as maleic anhydride modified products thereof, SIB, and SIBS are preferred. Among these, it is preferable in terms of productivity of a co-extruded film having layers A and B to use, as the elastomer (b2) of layer B, SIB or SIBS having the properties of the styrene-based block copolymer (a2) used in layer A and to blend the same type of styrene-based block copolymer (a2) in layers A and B.

[0043] When the total amount of the saponified ethylene-vinyl acetate copolymer (b1) and the thermoplastic elastomer (b2) in the B layer is taken as 100% by mass, the content of the thermoplastic elastomer (b2) is preferably 1 to 20% by mass, more preferably 2 to 15% by mass, and even more preferably 3 to 10% by mass. When the content is 1% by mass or more, the bending pinhole resistance is improved. When the content is 20% by mass or less, the deterioration of the gas barrier property and transparency of the present film is suppressed. Furthermore, when the content is low, the generation of gel during film formation is suppressed, which is preferable in terms of film productivity.

[0044] In layer B of this film, the thermoplastic elastomer (b2) is dispersed in the form of particles in the saponified ethylene-vinyl acetate copolymer (b1), with (b1) forming a sea-like dispersion and (b2) forming islands. Regarding the dispersion form, the maximum diameter of the (b2) particles in the horizontal direction is preferably 3.0 μm or less, more preferably 2.0 μm or less, and even more preferably 1.0 μm or less. The maximum diameter means the maximum diameter of the dispersed particles observed when the film is cut perpendicularly to the thickness direction and observed at a magnification of 2000 times by a cross-sectional stained TEM method. In layer B, the thermoplastic elastomer (b2) is dispersed in particles having a maximum diameter of 3.0 μm or less, thereby significantly improving the mechanical strength such as flexibility, impact resistance, and pinhole resistance due to bending of layer B, which mainly contains saponified ethylene-vinyl acetate copolymer (b1), which has poor flexibility and impact resistance, and also providing transparency.

[0045] In addition, even when a stretched film is produced, the thermoplastic elastomer (b2) in the saponified ethylene-vinyl acetate copolymer (b1) is not strongly stretched, and the aspect ratio (major axis / minor axis) of the length in the film thickness direction of the dispersed particles (major axis) to the length in the film horizontal direction (major axis) is preferably 1 to 3. When the present film has Layer A and Layer B, the dispersion of the styrene-based block copolymer (a2) in the aliphatic polyamide resin (a1) in Layer A and the dispersion of the thermoplastic elastomer (b2) in the saponified ethylene-vinyl acetate copolymer (b1) in Layer B combine to improve flexibility while maintaining transparency, and increase pinhole resistance against local stress concentration due to bending, enabling the film to exhibit good physical properties even in harsh environments at low temperatures.

[0046] General-purpose resins, additives, etc. Layer B may contain, in addition to the above-mentioned components (b1) and (b2), other components such as general-purpose resins and additives, to the extent that the properties of the film of the present invention are not impaired. The definition of the main components, additives, etc. are the same as for layer A.

[0047] <Layer configuration> The present film is sufficient to have at least one layer A containing an aliphatic polyamide resin (a1) and a styrene block copolymer (a2), and may have other layers. For example, it is possible to dispose a layer B containing the above-mentioned gas barrier resin, or an aliphatic polyamide resin layer (layer C) not containing a styrene block copolymer (a2), etc.

[0048] For example, in the case of a film configuration having a layer A and a layer B, a three-layer configuration such as layer A / layer B / layer A can be mentioned, and in the case of further having a layer C, preferred examples of the film include a four-layer configuration such as layer A / layer B / layer C / layer A, and a five-layer configuration such as layer A / layer C / layer B / layer C / layer A, or layer C / layer A / layer B / layer A / layer C. Preferred examples of the structure include a five-layer structure such as A layer / B layer / B layer / B layer / A layer or A layer / A layer / B layer / A layer / A layer, in which multiple A layers differ in type or content of the styrene block copolymer (a2) and / or multiple B layers differ in type or content of the thermoplastic elastomer (b2) are arranged, and a seven-layer structure such as C layer / A layer / B layer / B layer / B layer / A layer / C layer or C layer / A layer / A layer / B layer / A layer / A layer / C layer, but are not limited to these examples. In addition, an adhesive layer or other layers may be provided between the layers. Of the above layer configurations, from the viewpoints of improving the flex resistance of the film and recycling production efficiency, it is preferable to have a layer configuration having Layer A as the outermost layer.

[0049] From the viewpoints of pinhole resistance and oxygen gas barrier properties, it is preferable that the thickness ratio of layer A to the total film thickness is 30 to 90%, and that of layer B to 10 to 70%. When there are multiple layers A and / or layers B, these ratios are the ratios of the sum of the thicknesses of layers A and / or layers B to the total thickness. The thickness of each of the A layer, B layer, and C layer is not particularly limited, but is preferably 1 to 15 μm, more preferably 2 to 10 μm, and even more preferably 3 to 8 μm. When there are multiple A layers, B layers, and C layers, each layer may have a different thickness or the same thickness. The total thickness of the present film is not particularly limited, but in consideration of, for example, processability and practicality, the lower limit is preferably 10 μm or more, more preferably 12 μm or more. The upper limit is preferably 50 μm or less, more preferably 30 μm or less. If the total thickness of the present film is within the above range, the film has sufficient rigidity, and is excellent in mechanical properties such as bending pinhole resistance and impact resistance, and further, the film has excellent gas barrier properties.

[0050] From the viewpoint of mechanical properties and gas barrier properties, the present film is desirably a biaxially stretched film. As a method for biaxial stretching, any of the conventionally known stretching methods such as tenter type sequential biaxial stretching, tenter type simultaneous biaxial stretching, and tubular type simultaneous biaxial stretching can be used.

[0051] This film can generally be laminated with a polyolefin sealant film such as polyethylene. In this case, the layer located on the outermost layer side of the layer structure of this film can be subjected to a surface treatment such as corona treatment before lamination. In addition, an adhesive layer, metal foil, paper, etc. can also be laminated. Existing lamination methods can be used for lamination, such as dry lamination, wet lamination, sand lamination, and extrusion lamination. In addition to corona treatment, this film can also be subjected to surface treatments or surface processing such as printing, coating, and vapor deposition, as necessary.

[0052] From the viewpoint of maintaining the quality of the contents and preventing spoilage, the gas barrier properties and moisture resistance of the film of the present invention can be further improved by laminating a gas barrier resin layer thereon, or by depositing a metal such as aluminum or a metal oxide such as silicon oxide or alumina, or by applying a gas barrier coating agent such as polyvinyl alcohol (PVA).

[0053] <Manufacturing method> The present film can be produced by various methods, but for example, it is preferably produced by the following method. Both the aliphatic polyamide resin (a1) and the saponified ethylene-vinyl acetate copolymer (b1) are highly hygroscopic, and if a hygroscopic one is used, water vapor and oligomers will be generated when the raw material is melted and extruded, hindering film formation. Therefore, in preparing the raw material, it is preferable to dry it in advance to make the moisture content 0.1 mass% or less. In addition, various additives such as lubricants, antistatic agents, antioxidants, antiblocking agents, stabilizers, dyes, pigments, and inorganic fine particles can be appropriately used within the range that does not affect the properties of the film.

[0054] In the case of a multilayer film, the raw materials for each layer are melt-extruded by different extruders, and a substantially amorphous and unoriented film (hereinafter referred to as "unstretched film") is produced by a co-extrusion method. For example, the unstretched film can be produced by co-extrusion of the raw materials, in which the resins molten by the above-mentioned raw materials are joined in a feed block or a multi-manifold flat die or annular die, extruded as a multilayer film, and then quenched to produce a flat or annular unstretched film. In the case of a monolayer film, it is possible to produce an unstretched film by extruding using a known flat die or annular die.

[0055] Next, the unstretched film is stretched in the flow direction (machine direction, MD) of the film and in the width direction (transverse direction, TD) perpendicular thereto, preferably in one direction, usually 2.0 to 5.0 times, more preferably 2.0 to 5.0 times in each of the machine and transverse biaxial directions, and even more preferably 2.5 to 4.5 times in each of the machine and transverse biaxial directions. If the stretching ratios in each of the machine and transverse biaxial directions are less than 2.0 times, the effect of orientation by stretching is small and mechanical properties such as film strength are deteriorated, and if the stretching ratios in each of the biaxial directions are more than 5.0 times, the multilayer film is likely to break during stretching.

[0056] As the method of biaxial stretching, any of the conventionally known stretching methods such as tenter-type sequential biaxial stretching, tenter-type simultaneous biaxial stretching, and tubular-type simultaneous biaxial stretching can be used. For example, in the case of the tenter-type sequential biaxial stretching method, the unstretched film can be produced by heating the unstretched film to a temperature range of 40 to 100°C, stretching it in the longitudinal direction by 2.0 to 5.0 times using a roll-type longitudinal stretching machine, and then stretching it in the transverse direction by 2.0 to 5.0 times within a temperature range of 60 to 140°C using a tenter-type transverse stretching machine. In addition, in the case of the tenter-type simultaneous biaxial stretching method or the tubular-type simultaneous biaxial stretching method, the film can be produced by simultaneously stretching it in the longitudinal and transverse directions by 2.0 to 5.0 times within a temperature range of 60 to 200°C.

[0057] The biaxially stretched film is then heat-set to impart dimensional stability. The heat-setting temperature is preferably 200°C to 225°C, more preferably 205°C to 220°C. This makes it possible to obtain a stretched film with good room temperature dimensional stability and a desired heat shrinkage rate. The biaxially stretched film that has been sufficiently heat-set by the heat treatment operation can be cooled and wound up in the usual manner. If the heat setting temperature is within the above range, the heat setting is sufficiently performed, the laminate strength is maintained, and a film having sufficient impact resistance and bending pinhole resistance can be obtained, and an excellent film free from problems such as breakage and whitening of the film surface can be obtained.

[0058] In the present invention, in order to relieve the stress of crystallization shrinkage due to heat setting, relaxation is performed in the width direction during heat setting by 0 to 15%, preferably 3 to 10%, so that relaxation following the shrinkage of the film is sufficiently achieved and the film is relaxed uniformly in the width direction, resulting in a uniform shrinkage rate in the width direction and a film with excellent dimensional stability at room temperature.

[0059] In the present invention, after the relaxation, the film can be re-transversely stretched at a temperature of 140°C to 200°C in the range of 2 to 9%, preferably 3 to 7%, and more preferably 4 to 7%. If the re-transverse stretching temperature is within the above range, a suitable stress during stretching can be obtained, and uniform stretching is possible, so that the transverse shrinkage in the width direction becomes uniform. In addition, no heat setting is performed after stretching, and the transverse shrinkage is easily expressed. In addition, if the re-transverse stretching ratio is within the above range, a sufficient transverse shrinkage can be obtained to follow the solidification shrinkage of the sealant, the appearance of the sealed part is good, and a suitable shrinkage can be obtained, so that problems such as wrinkles and pattern misalignment can be prevented in the printing and lamination processes. The stretched film produced by the above method is cooled and wound up in a conventional manner.

[0060] <Film properties> (Oxygen gas barrier properties) This film has an oxygen permeability of 2.0cc / m at 23℃ and 50% relative humidity. 2 / 24h / atm or less is preferable, and 1.5cc / m 2 / 24h / atm or less is more preferable, and 1.0cc / m 2 / 24h / atm or less is more preferable, and an even lower value is desirable. 2 / 24h / atm or less is preferable because the film can maintain sufficient oxygen gas barrier properties as a packaging film to prevent deterioration of the contents and keep them fresh.

[0061] (Pinhole resistance (bending pinhole resistance)) This film was subjected to bending tests using a Gelbo flex tester under the following conditions: 3,000 bending tests at 23°C and 50% relative humidity, 500 bending tests at 5°C and 50% relative humidity, and 3,000 bending tests at 5°C and 50% relative humidity, and the number of pinholes that occurred was counted. Three tests were performed under each condition, and the average value was calculated. The number of pinholes was 15.0 per 481 cm under all conditions. 2 The following is preferable: 13.0 pieces / 481 cm 2 Less than 4.0 pieces / 481cm is more preferable. 2 Less than 3.0 pieces / 481 cm is more preferable. 2 Less than 1.0 piece / 481cm is more preferable. 2 The following is particularly preferable, and the fewer the better. In addition, the lower the environmental temperature, the less flexibility the film loses, so a smaller number of pinholes under low temperature conditions means better pinhole resistance. 15.0 pieces / 481 cm 2 If the thickness is less than this, pinholes are less likely to occur due to bending during transportation as a food packaging film or due to collisions between films, and oxidation deterioration of the contents due to a decrease in gas barrier properties is easily suppressed.

[0062] In addition, when this film is a multi-layer including layer B, the number of pinholes is 4.0 / 481 cm under all conditions. 2 Less than 3.0 pieces / 481 cm is preferable. 2 Less than 1.0 pcs / 481 cm is more preferable. 2 The following is even more preferable, and the fewer the better.

[0063] (transparency) The film of the present invention has a haze value of 10% or less, preferably 8% or less, more preferably 5% or less, and the smaller the value, the more preferable, as measured based on JIS K7136. If the total haze value is within this range, the film has excellent transparency, and has good design properties and visibility of contents when used as a packaging film.

[0064] (Hot water shrinkage rate) The hot water shrinkage rate of the present film at 95°C for 5 minutes is preferably 0.1% to 15% in both the machine direction (MD) and the transverse direction (TD). The lower limit is more preferably 0.3% or more, and even more preferably 0.5% or more. The upper limit is more preferably 10% or less, and even more preferably 5% or less. The hot water shrinkage rate at 127°C for 5 minutes is preferably 1% to 30% in both the machine direction (MD) and the transverse direction (TD). The lower limit is more preferably 3% or more, and even more preferably 5% or more. The upper limit is more preferably 25% or less, and even more preferably 23% or less. If the hot water shrinkage ratio is less than the above range, the heat setting temperature may be too high, and the impact resistance and bending pinhole resistance of the biaxially stretched film may be easily reduced. If the hot water shrinkage ratio exceeds the above range, the heat setting may be insufficient, and shrinkage may occur due to heat applied in post-processing such as printing, lamination, and bag making, which may cause misalignment during printing, wrinkles during lamination, and distortion of the bag product. A high hot water shrinkage is advantageous for low temperature pinhole resistance, but the mechanical strength of the film and the above-mentioned post-processability tend to be insufficient. The present invention has the effect that sufficient mechanical strength of the film can be obtained even with a low hot water shrinkage.

[0065] (Tensile stress at break, tensile elongation at break) The film has excellent mechanical strength, and the tensile stress at break in both the machine direction (MD) and the transverse direction (TD) is preferably in the range of 100 to 400 MPa, with the lower limit being more preferably 150 MPa or more, and even more preferably 200 MPa or more, as measured according to JIS K7127:1999 at a test speed of 200 mm / min and at -10°C and 23°C. If the film has a tensile stress at break in this range, the film will maintain its rigidity when packaged with contents, and will be less likely to develop pinholes or breaks due to bending. The tensile elongation at break measured according to JIS K7127:1999 at a test speed of 200 mm / min and at -10°C and 23°C is preferably 50% to 300% in either the machine direction (MD) or the transverse direction (TD), more preferably 60% or more, and even more preferably 75% or more. The film has excellent toughness when both the machine direction (MD) and the transverse direction (TD) are in the range.

[0066] (shock resistance) The present film has excellent impact resistance, and the breaking energy measured according to ASTM D3763 using a Hydroshot high speed tester at -10°C and 23°C is preferably 0.3 J or more, more preferably 0.5 J or more. A film having a breaking energy within this range is unlikely to break or develop pinholes even when subjected to impacts that occur during packaging of contents, for example, during transportation.

[0067] (Straight line cutting ability) It is preferable that when a straight line is drawn with a magic marker in the machine direction (MD) of the film and the film is torn for 200 mm along the straight line, the absolute value of the deviation from the straight line is 5.0 mm or less. EXAMPLES

[0068] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. The obtained films were evaluated by the following methods.

[0069] (1) Oxygen gas barrier properties The oxygen gas barrier property is measured by measuring the oxygen permeability (unit: cc / m) at 23℃ and 50% RH in accordance with JIS K7126 B method. 2 / 24h / atm) was measured.

[0070] (2) Pinhole resistance (flex resistance) The film was cut into pieces measuring 20cm x 28cm and left to stand for 24 hours or more under the conditions of the specified temperature and relative humidity of 50% shown below to adjust the temperature and humidity. The film was then subjected to repeated bending tests as follows using a Gelbo Flex Tester No. 901 manufactured by Rigaku Kogyosha, which complies with the MIL-B-131C standard, and the bending test was repeated until the film reached a bending strength of 481cm. 2 The number of pinholes per unit area was counted. The film was rolled into a cylinder of 20 cm in length and 28 cm in circumference, and one end of the rolled cylindrical film was fixed to the outer periphery of the disk-shaped fixed head of the tester, and the other end was fixed to the outer periphery of the disk-shaped movable head of the tester, overlapping by 5 mm in circumference. The fixed head and the movable head were opposed to each other with a distance of 17.5 cm.

[0071] Next, the movable head was rotated 440 degrees toward the fixed head while approaching it 8.8 cm along the axis of both heads facing parallel to each other, then moved straight forward 6.3 cm without rotating, and then these movements were reversed, and the bending test was performed a predetermined number of times in succession at a speed of 40 times per minute. After that, the area of ​​the part with the length of 17.5 cm between the fixed head and the movable head and the circumference of 27.5 cm excluding the overlapping part when made into a cylinder was 481 cm 2 Number of pinholes in the area (unit: number / 481cm 2 ) was measured by applying a voltage of 1 kV using a pinhole tester TRD model manufactured by Sanko Electronics Laboratory. The temperature, humidity, and number of bending tests were performed under three conditions: (i) temperature 5°C, relative humidity 50%, bending 500 times, (ii) temperature 5°C, relative humidity 50%, bending 3000 times, and (iii) temperature 23°C, relative humidity 50%, bending 3000 times. Three tests were performed under each condition, and the average value was calculated.

[0072] (3) Transparency The transparency was evaluated by measuring the haze (unit: %) in accordance with JIS K7136.

[0073] (4) Hot water shrinkage The film was cut out from both ends and three points in the center to a length of 120 mm in the longitudinal direction and 120 mm in the transverse direction, and three reference lines of more than 100 mm were drawn in each of the longitudinal and transverse directions (MD and TD). The sample was left to stand for 24 hours in an atmosphere of 23°C and 50% relative humidity, and the length of the reference lines was measured. The measured length before heat treatment was designated F. The sample was taken out after immersing in hot water at 95°C for 5 minutes, or after an autoclave test at 127°C for 5 minutes. After further standing for 30 minutes in an atmosphere of 23°C and 50% relative humidity, the length of the reference lines was measured, and the length after heat treatment was designated G. The average value of the hot water shrinkage rate (unit: %) of the three lines in the longitudinal and transverse directions was calculated using the following formula. (Formula) (FG) / F×100 (%)

[0074] (5) Tensile stress at break, tensile elongation at break Based on JIS K7127:1999, the tensile breaking stress (unit: MPa) and tensile breaking elongation (unit: %) in the machine direction and transverse direction (MD direction, TD direction) were measured at a test speed of 200 mm / min under conditions of -10°C and 23°C.

[0075] (6) Impact resistance The fracture energy (unit: J) was measured using a Hydroshot high-speed testing machine based on ASTM D3763 under ambient conditions of -10°C and 23°C.

[0076] (7) Straight cutting ability Two pieces of each size, 300mm in MD and 180mm in TD, are cut out from both ends and three points in the center of the obtained film, and straight lines exactly parallel to the MD are drawn with a magic marker at 30mm intervals. Next, cut these lines 50mm from the end using a feather blade to make a strip, and prepare the test piece. Next, place the test piece on a flat ground glass in front of the person measuring, with the MD facing straight ahead. Here, in the case of right-handed pulling, the right hand holds the strip part at the right end of the test piece, and the left hand holds the strip part next to it. Slowly pull the right hand holding the strip straight towards you. This action is repeated five times, starting from the right end. In the case of left-handed pulling, the opposite action is performed. The deviation from a straight line drawn in advance parallel to the MD at a point 200 mm from the start of the tear, i.e., a straight line was drawn in the MD and the absolute value of the deviation from the straight line when the film was torn for 200 mm, was taken as L (mm) and used as an index of linear cuttability. The above tests were carried out for both right-hand and left-hand pulls, and the average value (rounded off to one decimal place) was taken. The maximum value of the six points at both ends and in the center was used to perform the following evaluation. 〇: When L(mm) is 5.0mm or less ×: When L(mm) exceeds 5.0mm

[0077] (8) Dispersion form of elastomer The film was cut parallel to the machine direction (MD) and transverse direction (TD) of the film, and perpendicular to the film thickness direction, and the A layer was observed at three locations with a viewing angle of 8 x 8 μm at a magnification of 2000 times using cross-sectional staining TEM, and the maximum horizontal diameter (unit: μm) of the observed dispersed particles was measured. In addition, the aspect ratio (long diameter / short diameter) of the length of the dispersed particles in the film thickness direction (short diameter) to the length in the film horizontal direction (long diameter) was calculated.

[0078] <Raw materials used> (Aliphatic polyamide resin) N1: Polyamide 6 (relative viscosity (96% sulfuric acid) 3.34)

[0079] (Gas barrier resin) V1: Ethylene-vinyl acetate copolymer saponification product (EVOH) (ethylene content 25 mol%, saponification degree 99% or more) V2: Ethylene-vinyl acetate copolymer saponification product (EVOH) (ethylene content 32 mol%, saponification degree 99% or more)

[0080] (Thermoplastic elastomer) E1: Styrene-based elastomer, styrene-isobutylene-styrene block copolymer (SIBS) (styrene content 23% by mass, weight average molecular weight 95,000, type A durometer hardness 33) E2: Styrene-based elastomer, styrene-isobutylene-styrene block copolymer (SIBS) (styrene content 23% by mass, weight average molecular weight 93,000, type A durometer hardness 33) E3: Styrene-based elastomer, styrene-isobutylene-styrene block copolymer (SIBS) (styrene content 30% by mass, weight average molecular weight 88,000, type A durometer hardness 45) E4: Styrene-based elastomer, styrene-isobutylene-styrene block copolymer (SIBS) (styrene content 15% by mass, weight average molecular weight 146,000, type A durometer hardness 25) E5: Styrene-based elastomer, styrene-ethylene-butylene-styrene block copolymer (SEBS) (styrene content 20% by mass) E6: Polyamide elastomer, polyamide 12-polytetramethylene ether glycol copolymer E7: Polyolefin elastomer, maleic anhydride modified ethylene-butene 1-4-methylpentene copolymer

[0081] (Examples 1-2, Comparative Examples 1-4, Reference Examples 1-2) The resins indicated by the above abbreviations were compounded using a φ40 mm single screw extruder and extruded at a temperature of 250° C. to prepare a single-layer unstretched film having a thickness of 50 μm. The evaluation results are shown in Table 1.

[0082] (Examples 3 to 5, Comparative Examples 5 to 7, Reference Examples 3 to 4) The resin composition for layer A, in which the raw materials were blended in the mass ratio shown in Table 2, was fed into a φ40 mm single-screw extruder, and the resin composition for layer B was fed into a φ32 mm single-screw extruder. The resin molten by both extruders was divided by a distribution block and multilayered in a co-extrusion T-die. A molten film having a three-layer structure of layer A / layer B / layer A was extruded and quenched on a cooling roll at 30°C to produce an unstretched multilayer film. Next, the obtained unstretched multilayer film was stretched 3 times in the longitudinal direction using a roll-type longitudinal stretching machine at 55°C, and further stretched 3.5 times in the transverse direction using a tenter-type transverse stretching machine at 120°C. The obtained biaxially stretched film was then heat-set at 220°C, and then subjected to 5% transverse relaxation. After that, it was cooled to room temperature, both end portions corresponding to the gripping parts of the clip were trimmed, and the trimmed product film was wound into a roll to obtain a biaxially stretched multilayer film with layer A / layer B / layer A thicknesses of 5.5 μm / 4.0 μm / 5.5 μm and a total thickness of 15.0 μm. The evaluation results are shown in Table 2.

[0083] Example 6 The resin composition for layer A or C, in which the raw materials were mixed in the mass ratio shown in Table 2, was fed into a φ65 mm extruder, the resin composition for layer A was fed into a φ50 mm extruder, and the resin composition for layer B was fed into a φ50 mm extruder. Each molten resin composition was distributed in a distribution block and multilayered in a co-extrusion T-die, and a molten film with a five-layer structure of (Layer A or C) / Layer A / Layer B / Layer A / (Layer A or C) was extruded and quenched on a 30°C cooling roll to produce an unstretched multilayer film. Next, the obtained unstretched multilayer film was stretched 3 times in the longitudinal direction using a roll-type longitudinal stretching machine at 50°C, and further stretched 3.5 times in the transverse direction using a tenter-type transverse stretching machine at 120°C. The obtained biaxially stretched film was then heat-set at 210°C. Thereafter, it was cooled to room temperature, both ends corresponding to the parts held by the clips were trimmed, and the trimmed film was wound into a roll to obtain a biaxially stretched multilayer film with layer thicknesses of (A layer or C layer) / A layer / B layer / A layer / (A layer or C layer) of 3.5 / 2.0 / 4.0 / 2.0 / 3.5 μm and a total thickness of 15.0 μm. The evaluation results are shown in Table 2.

[0084] [Table 1]

[0085] [Table 2]

[0086] (Non-stretched monolayer film; Examples 1-2, Comparative Examples 1-4) The monolayer films of Examples 1 and 2 contain nylon 6, which is an aliphatic nylon, and SIBS having a styrene monomer unit content of 5% by mass or more and less than 30% by mass and a weight-average molecular weight of 20,000 or more and 130,000 or less, and are able to achieve both good transparency and low-temperature bending resistance. Comparative Example 1, which did not contain SIBS, and Comparative Example 2, which used SIBS with a styrene monomer content of 30 mass% or more, had poor low-temperature flex resistance. Comparative Example 3, which used SIBS with a weight-average molecular weight of more than 130,000, and Comparative Example 4, which used SEBS, had poor transparency.

[0087] (Biaxially oriented multilayer film; Examples 3 to 6, Comparative Examples 5 to 7) In the multilayer films of Examples 3 to 6 in which a B layer containing EVOH, a gas barrier resin, is arranged, the haze is 10.0% or less, and the number of pinholes resistant to bending at a temperature of 5°C and a relative humidity of 50% is 1.0 pinholes / 481 cm 2 Less than 1.0cc / m 2 We were able to obtain a film with an excellent balance of physical properties, including transparency, pinhole resistance while bending, and oxygen gas barrier properties, as well as good tensile properties, impact resistance, and straight cut properties, with a strength of less than 24h / atm. In addition, in Examples 3 to 6, the maximum horizontal diameter of the dispersed elastomer particles in layer A in a cross section parallel to TD and perpendicular to the film thickness direction was 3.0 μm or less and the aspect ratio was 2 or more, and the maximum horizontal diameter of the dispersed elastomer particles in layer A in a cross section parallel to MD and perpendicular to the film thickness direction was 4.0 μm or more. Figure 1(a) shows a schematic diagram of the TD-parallel cross section of layer A, and Figure 1(b) shows a schematic diagram of the MD-parallel cross section of layer A. In particular, in Example 6, even in a pinhole resistance test under harsh conditions of a temperature of 5°C, a relative humidity of 50%, and 3,000 bending cycles, the number of pinholes was only 0.2 / 481 cm. 2 It was an excellent film that had both oxygen gas barrier properties and transparency. At a temperature of 5°C, relative humidity of 50%, and 500 bending cycles, the film had a 0.2 particle / 481 cm 2 It is self-evident that: On the other hand, the three-layer films shown in Comparative Examples 5 to 7 had poor pinhole resistance due to bending. In Comparative Example 7, which used SIBS with a weight-average molecular weight of more than 130,000, the dispersion state of Layer A was poor, causing bumps and resulting in a poor film appearance.

[0088] (Reference examples 1~4) When a polyamide-based elastomer was used, the monolayer film of Reference Example 1 had high haze and poor transparency, but the multilayer film of Reference Example 3 had reduced haze due to the thinning of the film and elastomer caused by biaxial stretching. When polyolefin-based elastomer was used, the monolayer film of Reference Example 2 had good transparency and low-temperature bending resistance. However, due to the low affinity between aliphatic nylon and polyolefin-based elastomer, the multilayer film of Reference Example 4 experienced increased haze due to the generation of voids at the phase interface between the dispersed particles (islands) of the polyolefin-based elastomer and the nylon 6 (sea) after biaxial stretching. [Industrial Applicability]

[0089] The film of the present invention has excellent transparency and excellent pinhole resistance against bending over a wide temperature range from low temperature to room temperature, and therefore can improve the long-term storage stability of the packaged contents, and is effective in maintaining the quality of the packaged contents, such as food products and industrial parts, and reducing waste. [Explanation of symbols]

[0090] A1: Aliphatic polyamide resin A2: styrene-based block copolymer

Claims

1. A film having at least one layer A containing an aliphatic polyamide resin (a1) and a styrene-based block copolymer (a2), When layer A is taken as 100% by mass, the content of the styrene-based block copolymer (a2) is 1 to 20% by mass, the styrene-based block copolymer (a2) contains a styrene monomer unit and an isobutylene monomer unit as copolymerization components, the content of the styrene monomer unit being 5% by mass or more and less than 30% by mass, and the weight average molecular weight being 20,000 or more and 130,000 or less; The haze of the film is 10% or less, and At a temperature of 5°C, relative humidity of 50%, and 500 bending cycles, the number of pinholes was 15.0 / 481cm. 2 Is less than or equal to A polyamide resin film characterized by:

2. A biaxially stretched film having at least two layers, the layer A and a layer B containing a gas barrier resin, The number of pinholes was 4.0 / 481cm under the Gelboflex test conditions of 23°C, 50% relative humidity, and 3,000 bending cycles. 2 The polyamide resin film according to claim 1 , wherein the viscosity is less than 100 μm.

3. 3. The polyamide resin film according to claim 2, wherein the gas barrier resin of the layer B is a saponified ethylene-vinyl acetate copolymer (b1), the layer B contains the styrene-based block copolymer (a2), and the content of the styrene-based block copolymer (a2) is 1 to 20 mass% when the layer B is taken as 100 mass%.

4. 4. The polyamide resin film according to claim 1, wherein the styrene block copolymer (a2) is a styrene-isobutylene-styrene block copolymer.

5. 5. The polyamide resin film according to claim 1, wherein, in a cross-sectional observation parallel to the machine direction (MD) or width direction (TD) of the film, the maximum horizontal diameter of dispersed particles of the styrene block copolymer (a2) in the layer A in the MD or TD is 3.0 μm or less.

6. 6. The polyamide resin film according to claim 1, wherein the layer A is disposed as an outermost layer.

7. A packaging material using the polyamide resin film according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Resin material for blow molding, production of blow molded article and blow molded article

    JP1995310013A

  • Resin composition and molded product

    JP2005112889A

  • Polyamide-based resin laminate film and package using the same

    JP2015020393A

  • Thermoplastic elastomer composition and molding

    JP2018123216A

  • Laminate structure for barrier packaging

    WO2019081175A1